Overexpression of the Endothelial Protein C Receptor Is Detrimental during Pneumonia-Derived Gram-negative Sepsis (Melioidosis) - Kager, Liesbeth M.; Schouten, Marcel; Wiersinga, W. Joost; de Boer, J. Daan; Lattenist, Lionel C. W.; Roelofs, Joris J. T. H.; Meijers, Joost C. M.; Levi, Marcel; Dondorp, Arjen M.; Esmon, Charles T.; van 't Veer, Cornelis; van der Poll, Tom (PLoS neglected tropical diseases, 2013)
The endothelial protein C receptor (EPCR) enhances anticoagulation by accelerating activation of protein C to activated protein C (APC) and mediates anti-inflammatory effects by facilitating APC-mediated signaling via protease activated receptor-1. We studied the role of EPCR in the host response during pneumonia-derived sepsis instigated by Burkholderia (B.) pseudomallei, the causative agent of melioidosis, a common form of community-acquired Gram-negative (pneumo)sepsis in South-East Asia. Soluble EPCR was measured in plasma of patients with septic culture-proven melioidosis and healthy controls. Experimental melioidosis was induced by intranasal inoculation of B. pseudomallei in wild-type (WT) mice and mice with either EPCR-overexpression (Tie2-EPCR) or EPCR-deficiency (EPCR(-/-)). Mice were sacrificed after 24, 48 or 72 hours. Organs and plasma were harvested to measure colony forming units, cellular influxes, cytokine levels and coagulation parameters. Plasma EPCR-levels were higher in melioidosis patients than in healthy controls and associated with an increased mortality. Tie2-EPCR mice demonstrated enhanced bacterial growth and dissemination to distant organs during experimental melioidosis, accompanied by increased lung damage, neutrophil influx and cytokine production, and attenuated coagulation activation. EPCR(-/-) mice had an unremarkable response to B. pseudomallei infection as compared to WT mice, except for a difference in coagulation activation in plasma. Increased EPCR-levels correlate with accelerated mortality in patients with melioidosis. In mice, transgenic overexpression of EPCR aggravates outcome during Gram-negative pneumonia-derived sepsis caused by B. pseudomallei, while endogenous EPCR does not impact on the host response. These results add to a better understanding of the regulation of coagulation during severe (pneumo)sepsis.